Voldemārs Langenfelds: intervija ar Alfonu Piterānu. - Jamonte, Daiga (My University, 2023)
Par godu botāniķa, ābeļu ģints (Malus Mil.) pētnieka Voldemāra Langenfelda 100 gadu jubilejai Latvijas Universitātes Muzejs organizēja sarunu ar viņa draugu un kolēģi Dr. habil. biol. Alfonu Piterānu. Sarunu vadīja LU Muzeja krājuma glabātāja Daiga Jamonte.
Voldemar Langenfeld. Interview with Alfons Piteran.
In honor of the 100th anniversary of the botanist, researcher of the apple genus (Malus Mil.)Voldemārs Langenfelds, the Museum of the University of Latvia organized a conversation with his friend and colleague Dr. able biological Alfon Piteran. The conversation was led by Daiga Jamonte, custodian of the collection of the Museum of the UL.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Botānika; botany; Alfons Piterāns; Latvijas Universitātes Bioloģijas fakultāte; biogrāfija; biography; mutvārdu vēsture; intervija; interview